ENGLISH LANGUAGE TRAINING FOR PAKET C LEARNING PARTICIPANTS TO IMPROVE THEIR SPEAKING ABILITY - Nunu Mahmud Firdaus (IKIP Siliwangi Bandung, 2018)
The purpose of this study is to describe the process of tutoring, describe the results of learning English, and find out the effect of learning guidance on speaking skills of Paket C learning participants in PKBM (Society Learning Centre) Sukabaru. The research method used is descriptive qualitative through data triangulation. Data is collected using test techniques to obtain data about the results of English speaking skill of learning community before and after being given tutorial through trainings. The results of the study show that learning guidance influences the results of English learning in term of speaking skills. Through the training of English speaking, the participants show improvement in mastering English with indicators of mastering many English vocabularies, and being able to speak fluently. On English language training, the researcher conducts the observations on speaking English demonstration and the participants can apply speaking comprehension.